2020
DOI: 10.1111/trf.16134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the appropriateness of platelet transfusions compared with evidence‐based platelet guidelines: An audit of platelet transfusions at 57 hospitals

Abstract: Background: Platelet transfusions are used to prevent or control bleeding in patients with thrombocytopenia or platelet dysfunction. The pretransfusion platelet count threshold has been studied extensively in multiple patient settings yielding high-quality evidence that has been summarized in several comprehensive evidence-based platelet guidelines. Study Design and Methods: A prospective 12-week audit of consecutive platelet transfusions using validated and evidence-based adjudication criteria was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
(126 reference statements)
1
8
2
1
Order By: Relevance
“…In our study, we showed that approximately 56% of all PC transfusions were not compliant with the most recent PC transfusion guidelines [ 2 ]. This percentage is higher than published by authors who showed that 41.5% of adult PC orders were deemed inappropriate [ 21 ]. Reported reasons for overriding blood transfusion guidelines were diverse, including acute bleeding (>34%), protocolized behaviors on specialty services (up to 26%), “symptomatic” anemia (11–12%), anticipated surgical/procedural intervention (10–15%), and imminent hospital discharge (2–5%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In our study, we showed that approximately 56% of all PC transfusions were not compliant with the most recent PC transfusion guidelines [ 2 ]. This percentage is higher than published by authors who showed that 41.5% of adult PC orders were deemed inappropriate [ 21 ]. Reported reasons for overriding blood transfusion guidelines were diverse, including acute bleeding (>34%), protocolized behaviors on specialty services (up to 26%), “symptomatic” anemia (11–12%), anticipated surgical/procedural intervention (10–15%), and imminent hospital discharge (2–5%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 55%
“…In the study by Hill-Strathy et al, the most common clinical scenario where PC transfusion was considered inappropriate (53% of inappropriate orders in adults) was prophylaxis in the absence of bleeding or before the planned procedure in patients with hypo-proliferative thrombocytopenia and a platelet count over 10 × 10 9 /L [ 21 ]. The percentage of inappropriate PC transfusions in our study was much higher than in the population of hematology patients, in whom only 28% of transfusions were performed outside of guidelines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlighted a significant percent of fresh frozen plasma transfused inappropriately (54%) due to its use as a volume expander and also in the settings of normal coagulation tests, seen similarly in an audit conducted by Wade et al 15 Present study showed platelets to be the most inappropriately transfused component (57%). Widespread platelets as prophylaxis in absence of bleeding attribute to a significant percentage of inappropriate transfusion as concluded by Hill-Strathy et al 16 There is limited data about blood component transfusions audit in children as compared to adults and scarce data is available at the national level. This audit has been conducted only in the paediatric intensive care setting of a tertiary care hospital in a time frame of two months; a larger study population and duration are required to infer better study results.…”
Section: Discussionmentioning
confidence: 99%
“…혈소판 수혈은 부족한 혈소판 성분을 보충함으 로써 출혈을 치료(지혈)하고 예방하는 데 그 목적 이 있다. 일반적으로 혈소판 수혈의 가장 흔한 적 응증은 저증식성혈소판감소증(hypoproliferative thrombocytopenia)을 보이는 혈액종양 환자들에서 보 존적 치료 목적의 수혈로 전체 혈소판 수혈 적응 증의 46%에서 77%까지 차지하는 것으로 보고되 었다 [1][2][3]. 최근 혈액종양 환자의 증가와 관련하 여 치료의 강도와 기간의 증가 및 생존률 증가로 갈수록 혈소판제제의 사용량이 증가하고 있는 추 세이다 [4].…”
Section: 서 론unclassified